2015
DOI: 10.1007/s10802-015-9973-2
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Parenting Styles in Early Childhood Differentially Influence Neural Response to Peer Evaluation in Adolescence

Abstract: Behavioral inhibition (BI) is a temperament characterized by social reticence and withdrawal from unfamiliar or novel contexts and conveys risk for social anxiety disorder. Developmental outcomes associated with this temperament can be influenced by children’s caregiving context. The convergence of a child’s temperamental disposition and rearing environment is ultimately expressed at both the behavioral and neural levels in emotional and cognitive response patterns to social challenges. The present study used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 61 publications
5
57
0
Order By: Relevance
“…35 For each of the four time points, observed behavioral and maternal report measures were standardized in the full cohort and then averaged to create a single measure of early childhood BI. 9,36,37 For our primary analyses, we used this continuous composite measure of early childhood BI and social reticence. This composite provides a stable measure of early childhood BI and has been used extensively in prior work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 For each of the four time points, observed behavioral and maternal report measures were standardized in the full cohort and then averaged to create a single measure of early childhood BI. 9,36,37 For our primary analyses, we used this continuous composite measure of early childhood BI and social reticence. This composite provides a stable measure of early childhood BI and has been used extensively in prior work.…”
Section: Methodsmentioning
confidence: 99%
“…This composite provides a stable measure of early childhood BI and has been used extensively in prior work. 11,12,36,37 For a secondary analysis to compare results with other studies, we categorized participants on the basis of their reactivity profiles at 4 months of age. This analysis attempts to replicate findings from the only other longitudinal structural brain study of young adults with histories of BI in infancy.…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that warm and supportive parenting earlier in adolescence may have neuroprotective effects on adolescent brain development. Furthermore, two recent studies showed that the quality of parenting can influence how adolescents respond to peer feedback, with negative parenting attenuating striatal responsiveness to peer acceptance (Tan et al, 2014) and positive parenting attenuating striatal reactivity to peer rejection (Guyer et al, 2015). These findings demonstrate that, given continued plasticity in the neural circuitry that supports affective behavior during adolescence, relationships with parents remain influential on how adolescents process and manage both positive and negative emotional experiences.…”
Section: The Emotional Adolescent Brain In Contextmentioning
confidence: 99%
“…In a longitudinal study of children from the ages of 4-15, those with parents who reported use of more supportive practices displayed a slower increase in the development of internalizing problem behaviors as compared to peers with parents employing less supportive practices (Williams et al, 2009). More recently, in a neuroimaging study, after experiencing peer rejection, adolescents with a history of AW, and who had parents who reported use of more supportive practices, displayed less activation in the brain region associated with fear and anxiety than counterparts with parents who reported less use of supportive practices (Guyer et al, 2015). This suggests that supportive parenting practices can buffer children exhibiting more AW from having as strong of a negative emotional response to negative social appraisal -possibly through the development of higher stress tolerance and confidence.…”
Section: Contribution Of Parenting Practicesmentioning
confidence: 99%
“…Broadly speaking, less supportive parenting practices are considered risk factors for all children, but especially those who display their own personal risk factors such as high levels of AW (Guyer et al, 2015;Pluess & Belsky, 2010). For instance, given that these children are more hypervigilant, anxious, and sensitive to criticism than peers, insecurity and stress are likely to increase when caregivers place high demands, but do not provide adequate emotional responsiveness to support the child in meeting them (Darling & Steinberg, 1993).…”
Section: Contribution Of Parenting Practicesmentioning
confidence: 99%